Phospholipid association with the bovine cardiac mitochondrial adenosine triphosphatase. - Brown, R E (1985)
The association of different phospholipids with a lipid-depleted oligomycin-sensitive ATPase from bovine cardiac mitochondria [Serrano, Kanner & Racker (1976) J. Biol. Chem. 251, 2453-2461] has been examined using three approaches. First, reconstitution of the ATPase with different synthetic diacyl phospholipids resulted in a 2-10-fold stimulation of ATPase specific activity depending upon the particular phospholipid employed. The phospholipid headgroup region displayed the following order of ATPase reactivation potential: dioleoylphosphatidylglycerol greater than dioleoylphosphatidic acid greater than dioleoylphosphatidylcholine. Furthermore, the ATPase showed higher levels of specific activity when reconstituted with dioleoyl phospholipid derivatives compared with dimyristoyl derivatives. Second, examination of the phospholipid remaining associated with the lipid-depleted ATPase upon purification showed that phosphatidylcholine, phosphatidylethanolamine, and diphosphatidylglycerol were present. No relative enrichment of any of these phospholipids (compared with their distribution in submitochondrial particles) was noted. Therefore, no preferential association between the ATPase and any one phospholipid could be found in the mitochondrial ATPase. Third, the sodium cholate-mediated phospholipid exchange procedure was employed for studying the phospholipid requirements of the ATPase. Replacement of about 50% of the mitochondrial phospholipid remaining with the lipid-depleted ATPase could be achieved utilizing either synthetic phosphatidic acid or phosphatidylcholine. Examination of the displaced mitochondrial phospholipid showed that phosphatidylcholine, phosphatidylethanolamine, and diphosphatidylglycerol were replaced with equal facility.